Pineapple Utilization as Raw Materials of Bioethanol Production Using Simultaneous Saccharification and Fermentation Method - Utomo, Pramono Putro (Balai Riset dan Standardisasi Industri Pontianak, 2011)
The research of pineapple utilization as raw materials of bioethanol production using simultaneous saccharification and fermentation (SSF) method has been done. The purpose of this research was to increase the utilization of pineapple as raw material for bioethanol also to obtain the effect of microbial species used and the length of fermentation on the yield of bioethanol. The treatments conducted were species of microbe and the length of fermentation. The results showed that the treatment of multiple microbial cultures of Aspergillus niger, Saccharomyces cerevisiae, and Zymomonas mobilis (1:1:1) with 24-hour long fermentation produce ethanol yield and the optimal concentration of 50,680 ml/kg and 6.335%.